Partial deligandation activated ZIF-67 for efficient electrocatalytic oxygen reduction reaction - Yang, Xiaoli; Gu, Jiali; Liu, Chenhong; Bai, Zhengyu; Yang, Lin (Frontiers in Chemistry, 2022)
Removing the blocked molecular groups and fully exposing the intrinsic active sites of metal-organic frameworks (MOFs) could give full play to their advantages of multi-active sites and multi-channel mass transfer, which will be benefit to the electrocatalytic oxygen reduction reaction(ORR) in fuel cell. Here, the partial diligandation activated ZIF-67 (named as ZIF-67-400) with excellent ORR performance are obtained by a simple low-temperature pyrolysis. The ORR electrocatalytic activity exhibits a half-wave potential of 0.82 V and the stability of maintaining 96% activity after 10 h operation, which is comparable to commercial Pt/C. Further researches reveal that the morphology, special dodecahedron configuration and crystal structure of ZIF-67-400 maintain well during the pyrolysis, but some hydrocarbon groups in the ligands are eliminated, resulting in that the active sites are exposed and coordinated with the intrinsic porosity, improving the catalytic performance. This work may open a alternative path for activating the electrocatalytic performance of metal-organic framework by low temperature annealing precess.